Nutrition Studies on Eucalyptus. III. Diagnosis of Mineral Deficiencies in Eucalyptus grandis Seedlings - Kaul, O. N.; Srivastava, P. B. L.; Tandon, V. N. (Indian Forester, 1968)
The paper describes the effect of some macro-nutrient deficiencies on the growth and morphology of Eucalyptus grandis seedlings. The results indicate that deficiency of nitrogen caused stunted growth, strong chlorosis, necrosis, premature defoliation and abaence of branching, while seedlings under phosphorus deficiency, had a characteristic appearance by producing thin lateral and secondary branches with numerous small leaves, towards the end of the growing season.